Predictive value of the monocyte count for determining the risk of postoperative moderate-to-severe ARDS in patients undergoing one-lung ventilation during radical treatment of esophageal cancer - Zhang, Feng; Lu, Shunmei; Wang, Guilong; Xu, Hongyang; Huang, Dongxiao; Li, Xiaomin (Frontiers in Medicine, 2025)
BackgroundThis study aimed to screen for risk factors and to assess the predictive value of the monocyte count for the development of moderate-to-severe acute respiratory distress syndrome (ARDS) in patients undergoing one-lung ventilation (OLV) during radical surgery for esophageal cancer.MethodsIn this retrospective study, patients with esophageal cancer admitted to the Department of Thoracic Surgery of Wuxi People’s Hospital between January 2017 and January 2021 were selected. Demographic, preoperative, intraoperative, and postoperative (within 2 h) data were collected. Patients were categorized into moderate-to-severe ARDS and non-moderate-to-severe ARDS groups. Multifactorial logistic regression, receiver operating characteristic (ROC), curve-fitting, and Spearman correlation analysis were used to analyze the data.ResultsAfter screening, 255 patients were enrolled, with 18% in moderate-to-severe ARDS group. Regression analysis revealed that postoperative monocyte count was an independent predictor for severe ARDS after surgery (OR = 2.916, 95% CI: 1.082–7.863, p < 0.05). The optimal cut-off value of postoperative monocyte count in predicting moderate-to-severe ARDS was 0.56 × 109/L (AUC = 0.708) with a sensitivity of 67.4% and a specificity of 66.5%. The difference of predictive value between postoperative monocyte count and prediction model (AUC = 0.760) was not statistically significant (p = 0.142). Additionally, a nonlinear connection between postoperative monocyte count and severe ARDS was found using curve fitting.ConclusionThe postoperative monocyte count is an ideal predictor of postoperative moderate-to-severe ARDS in this patient population and can be used for the early diagnosis of patients with severe postoperative ARDS.